Comparison between the different new anti-coagulants for non-valvular atrial fibrillation: network meta-analysis - Albutti, Hala Mohammed (International Journal of Basic & Clinical Pharmacology, 2019)
Atrial fibrillation is associated with high risk of ischaemic stroke which is considered a major fatal complication in atrial fibrillation. That’s why, anticoagulants were used to prevent this major complication. However, anticoagulants themselves are associated with their own complications. A systematic search of Embase, Medline and Google scholar were conducted. The included papers were extracted for outcomes related to the complications of each drugs. A Bayesian network meta-analysis based on Markov chain Monte Carlo simulation (MCMC) with 10000 burn-in iterations and 50000 inference iterations. We found eighteen papers that fit our inclusion criteria. Apixaban had the least risk of major bleeding compared to Warfarin [HR = 0.536, 95% (0.448, 0.652)] and the least risk of gastrointestinal hemorrhage. For stroke risk, the Rivaroxaban had the least risk compared to Warfarin [HR = 1.05, 95% (0.98, 1.14)]. For intracranial hemorrhage, dabigatran had the least risk of intracranial haemorrhage compared to Warfarin [HR = 0.46, 95% CrI (0.36, 0.61)]. For the thromboembolism risk, other non-vitamin k antagonist had the least risk of intracranial haemorrhage compared to Warfarin [HR = 0.523, 95% (0.095, 2.85)]. There were no conclusive results about the best anticoagulant drugs for non-valvular atrial fibrillation. Apixaban was the least among them to be associated with major bleeding, while rivaroxaban was ranked the first with least stroke complications. Furthermore, dabigatran was associated with less risk of intracranial haemorrhage compared to other anticoagulants.